Interface formation and Mn segregation of directly assembled La0.8Sr0.2MnO3 cathode on Y2O3-ZrO2 and Gd2O3-CeO2 electrolytes of solid oxide fuel cells - He, S.; Chen, K.; Saunders, M.; Quadir, Z.; Tao, S.; Irvine, J.; Cui, C.; Jiang, San Ping (Elsevier BV * North-Holland, 2018)
© 2018 The establishment of intimate electrode/electrolyte interface is very important in solid oxide fuel cells (SOFCs), because it plays a critical role in the overall cell performance and durability. In this study, Mn segregation and interface formation between directly assembled La0.8Sr0.2MnO3(LSM) electrode and yttrium-stabilized zirconia (YSZ) or gadolinium-doped ceria (GDC) electrolytes are studied using combined focused ion beam and scanning transmission electron microscopy (FIB-STEM). In the case of LSM/YSZ and LSM/GDC electrodes, a significant reduction in the electrode ohmic resistance is observed after cathodic polarization at 900 °C and 500 mA cm-2, indicating the formation of an intimate interface. However, LSM particles start to disintegrate at the electrode/electrolyte interface with the increase of polarization time in the case of LSM/YSZ electrode. On the other hand, the LSM/GDC interface is very stable with negligible microstructure change at the interface. Mn segregation from the LSM perovskite structure is identified under the influence of polarization in both LSM/YSZ and LSM/GDC electrodes. The results demonstrate that nature of the electrolyte plays a critical role in the electrochemical activity, microstructure, morphology and stability of LSM/electrolyte interface under SOFC operation conditions.